Evaluating architectural design schemes for Anganwadi Centre in Ajjarkad, Karnataka, India by architectural students through community participatory methods - Ang, Susan; Nandineni, Ramadevi; Mohd Nawawi, Norwina (Springer, Cham, 2021)
Anganwadi is a holistic health and education initiative that provides basic health care, nutrition and educational programs to rural mothers and children. It is part of the Indian Government’s Integrated Child Development Services (ICDS) Scheme, introduced in 1975 and is today one of the largest child development initiatives in the world. The early developmental years of children aged 0-6 years spent in an Anganwadi or equivalent early learning centre influences children’s physical, emotional and intellectual development. A child not only engages in active learning but also engages in passive learning from its physical and environmental surroundings for which is manifested in the architectural design of the building. A collaboration between architecture students from three universities in India, Australia and Malaysia as well as the office of the Deputy Director of Women and Child Welfare, Udupi District was initiated in 2018 for the proposed design of a purpose-built Anganwadi centre for Ajjarkad, Karnataka. The project was executed through a student global learning program known as iDiDe (Intercultural dialogue through design). This study evaluates the seven design schemes created with Ajjarkad community input and co-design participatory methods based upon sustainable integrated architectural parameters, including space efficiency, environmental resilience, children physical rating scale and cultural value. The issue of “fit for purpose” and “architecture design robustness” and subsequent construction of an Anganwadi centre are rarely interrogated at an integrated design level. In evaluation, this paper discusses the synthesis of architectural design, the pedagogy and cultural attributes that aid the formulation of architectural design parameters for Anganwadi building. The study found that through co-design participatory methods, the design process was shaped through community engagement and the outcomes thus satisfied the stakeholders as fit for purpose.